On the behavior of inhaled fibers in a replica of the first airway bifurcation under steady flow conditions. Issue 4 (2nd March 2022) - Lizal, Frantisek; Cabalka, Matous; Maly, Milan; Elcner, Jakub; Belka, Miloslav; Lizalova Sujanska, Elena; Farkas, Arpad; Starha, Pavel; Pech, Ondrej; Misik, Ondrej; Jedelsky, Jan; Jicha, Miroslav
Abstract: Inhaled fibers can potentially cause inflammation of the lung tissue and interstitium, which after long-term exposure may lead to lung cancer, malignant mesothelioma, or pulmonary and pleural fibrosis. To reduce the risk and set the appropriate occupational hygiene regulations, it is important to be able to precisely calculate the fate of inhaled fibers depending on their physical characteristics and inhalation conditions. In the absence of experimental data on the real behavior - trajectories, orientation and flipping - of inhaled fibers, a new test rig was assembled for visualization and recording of flowing fibers in a replica of the human trachea and the first bronchial bifurcation. Fibers prepared from commercially produced glass fibers have been processed, dispersed, and introduced into the airway replica. Visualization was performed using a powerful LED light and a high-speed camera. The flow of fibers was evaluated upstream and downstream of the realistic asymmetrical bifurcation and dependence on flow conditions was sought. The fractions of parallelly and perpendicularly flowing fibers were statistically evaluated in three locations. The frequency of flipping was also analyzed. The results show that the parallel orientation of the fibers is less dominant than expected. The fiber orientation tables for various conditions can be used to adjust and improve computational simulations of inhaled fibers in the human airways.